2017
DOI: 10.1103/physreva.95.023807
|View full text |Cite
|
Sign up to set email alerts
|

Creation of two-photon states via interactions between Rydberg atoms during light storage

Abstract: We propose a new method to create two-photon states in a controllable way using interaction between the Rydberg atoms during the storage and retrieval of slow light. A distinctive feature of the suggested procedure is that the slow light is stored into a superposition of two atomic coherences under conditions of electromagnetically induced transparency (EIT). Interaction between the atoms during the storage period creates entangled pairs of atoms in a superposition state that is orthogonal to the initially sto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Thus, the combination of the strong DDI of Rydberg atoms and the high optical nonlinearity of EIT can efficiently mediate the interaction between photons via Rydberg polaritons in the dipole blockade regime, where the Rydberg polariton is the collective excitation involving the light and the atomic coherence between the ground and Rydberg states [15,16]. The Rydberg-EIT mechanism can lead to the applications of quantum optics and quantum information processing [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the combination of the strong DDI of Rydberg atoms and the high optical nonlinearity of EIT can efficiently mediate the interaction between photons via Rydberg polaritons in the dipole blockade regime, where the Rydberg polariton is the collective excitation involving the light and the atomic coherence between the ground and Rydberg states [15,16]. The Rydberg-EIT mechanism can lead to the applications of quantum optics and quantum information processing [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [28], J. Ruseckas et al proposed a method to create two-photon states by making pairs of Rydberg atoms entangled during the storage.…”
Section: Introductionmentioning
confidence: 99%
“…This effect, if the nonlocal mechanism had not been identified, might indeed be interpreted as simply manifesting a position-momentum quantum uncertainty with respect to directions perpendicular to the down-converted photon propagation. It is also interesting to conjecture whether effects of a similar kind might play a role in the creation of two-photon states through interactions between Rydberg atoms [100]. It remains to be seen what other forms of photon-pair nonlocality might prove amenable to experimental determination; the possible implications for quantum entanglement between emitted photons is a subject now under further active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Quite recently, important experimental progress has been achieved on light storage and retrieval in EIT media of cold [33][34][35] or thermal [36] Rydberg atoms. It is found that a multiphoton pulse can be engineered to exhibit such peculiar properties as Rydberg-mediated interactions [33] and two-photon states [37]. However, a satisfactory theoretical method to reproduce relevant experimental results is still lacking, although several * jhwu@nenu.edu.cn methods [38][39][40][41][42] have been proposed to deal with the dynamic propagation of single-photon or few-photon pulses in Rydberg-EIT media.…”
Section: Introductionmentioning
confidence: 99%